FRACTURES OF THE RIBS AND THE DIAPHRAGMATIC RUPTURE WITH A FORMATION OF THE TRANSDIAPHRAGMATIC INTERCOSTAL HERNIA AS A RESULT OF SEVERE COUGHING (CLINICAL OBSERVATION WITH A REVIEW OF THE LITERATURE) - S. N. Danielyan; M. M. Abakumov; R. S. Muslimov; I. E. Galankina; A. P. Vilk (Неотложная медицинская помощь)
ABSTRACT. Severe coughing might lead to development of a number of complications, including the diaphragmatic rupture and the ribs fractures. The report contains two similar rare clinical cases: male patients aged 48 and 74 years with transdiaphragmatic intercostal thoracic wall hernia after the rupture of the left half of the diaphragm and ribs fractures as a result of violent coughing. Both patients had a late diagnosis of injuries. Surgical therapy was performed via thoracotomy access using a mesh implant. histological study of the rib in the damaged area in one case detected fibrous osteodysplasia. The review of literature on this rare type of injury was analyzed.